IMPELEMENTASI TERHADAP BUDAYA TOLERANSI DAN PERDAMAIAN DALAM KEHIDUPAN SEHARI-HARI DI MA’HAD AL ZAYTUN - Adrian Nugraha, Rizal; Supriyatno; Bin Sirwan , Supriyatno; Zahira, Tiara (Cahaya Ilmu Bangsa Institute, 2024)
This research discusses the implementation of a culture of tolerance and peace in daily life at Ma’had Al Zaytun, a pesantren located in Indramayu Regency, West Java, Indonesia. The Al Zaytun Institute emphasizes the importance of these two fundamental principles in creating a harmonious and conducive environment for learning. Through character education integrated into the curriculum, extracurricular activities that encourage cooperation and interfaith dialogue, as well as an inclusive learning environment, Ma’had Al Zaytun has successfully instilled values of tolerance and peace in its students. This research employs a literature study method through theoretical and empirical reviews from various sources, including books, journal articles, research reports, and official documents related to multicultural education and the teaching of tolerance values in educational institutions. Research findings indicate that tolerance and peace are taught through inclusive religious education, social activities, and interactions among students that encourage appreciation for differences. The curriculum at Ma’had Al-Zaytun combines religious education with multicultural insights, instilling the importance of living together peacefully. Additionally, social interactions among students from diverse backgrounds serve as an effective medium for fostering mutual respect and cooperation. This culture of tolerance is also supported by the active role of teachers who serve as role models in maintaining harmony within the Ma’had environment. However, even though it has succeeded in creating a conducive atmosphere for peace, Ma’had Al-Zaytun faces challenges in maintaining the consistency of these values amidst external influences that often bring sentiments of intolerance. In conclusion, Ma’had Al-Zaytun is capable of being an effective model of education based on tolerance and peace in shaping the character of a young generation that is inclusive and loves peace. Keywords: Culture; Peace; Tolerance